TORREFACTION OF OIL PALM FROND LEAVES AND STEMS UNDER COMBUSTION GAS AND INERT NITROGEN ATMOSPHERES - PREMCHAND, PREMCHAND (2019)
Torrefaction is a low temperature thermal pretreatment of lignocellulosic biomass at temperatures between 200 and 300 °C under an inert environment, which has been shown tobe effective for enhancing the quality of the biomass for use not only as a solid fuel, such as its energy content and shell life, but also to prepare it as a feedstock for further degradation such as pyrolysis and gasification. Torrefaction is commonly performed under an inert nitrogen atmosphere so as to minimize the gasification loss as much as possible. However, a continuous supply of inert gas such as purified nitrogen (N2) makes this process costly and the use of combustion gas like industrial flue gases has been proposed.